2015
DOI: 10.21608/ejap.2015.93640
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Progestin Source on Some Blood Biochemical Constituents of Dromedary She-Camels During Induction of Ovulation in the North Western Coast of Egypt

Abstract: Eighteen one-humped she-camels were divided randomly into three equal groups: group 1 served as control; group 2 (MGA) received (0.5 mg/ head/day) of Melengestrol acetate for 10 days and; group 3 (CIDR) were fitted intravaginally with controlled internal drug release (CIDR, 1.38g P 4) for 10 days. At day 10 the MGA and CIDR groups were administered PGF 2α and 3000 IU PMSG, MGA feeding was withdrawn and CIDRs were removed. Animals were given 5000 IU of hCG 10 days later and were artificially inseminated (day 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
1
1
Order By: Relevance
“…However, value of plasma T3 was not affected throughout follicular phase of the cycle status. This finding is in agreement with previous reports on dromedary camels (Ali et al 2011;Abd El-Hamid et al 2015) as they reported that, the increased of E2 concentration due to the found of dominant follicle size (1.2-1.8cm) during mature ovarian phase (Atigui et al 2014), the concentration of E2 secretion is around (317.8-444.4pg/mL), whereas P4 concentration remains below (1ng/mL) during the follicular phase. Additionally, in dromedary she-camels, a higher significant correlation was found between E2 levels and follicular size during mature phase.…”
Section: Changes In Blood Biochemical Constituents and Hormonal Profiles During Cycle Statussupporting
confidence: 93%
See 2 more Smart Citations
“…However, value of plasma T3 was not affected throughout follicular phase of the cycle status. This finding is in agreement with previous reports on dromedary camels (Ali et al 2011;Abd El-Hamid et al 2015) as they reported that, the increased of E2 concentration due to the found of dominant follicle size (1.2-1.8cm) during mature ovarian phase (Atigui et al 2014), the concentration of E2 secretion is around (317.8-444.4pg/mL), whereas P4 concentration remains below (1ng/mL) during the follicular phase. Additionally, in dromedary she-camels, a higher significant correlation was found between E2 levels and follicular size during mature phase.…”
Section: Changes In Blood Biochemical Constituents and Hormonal Profiles During Cycle Statussupporting
confidence: 93%
“…In accordance with the present results, Khalifa (2012) reported that plasma ALT enzyme activity increased during post-partum months in camels, while AST enzyme activity did not change. Saeed et al (2009) reported that the changes in transaminases might be due to gluconeogenesis enhancement in some muscle and liver cells, but the observed changes in plasma ALT activity in this study are within in normal range of camel (Abd El-Hamid et al 2015). Also, in this study plasma ALP activity increased significantly during second and third trimesters of lactation period.…”
Section: Changes In Blood Biochemical Constituents and Hormonal Profiles During Lactation Periodcontrasting
confidence: 68%
See 1 more Smart Citation